2017
DOI: 10.1111/apm.12640
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic perspective of the oxido‐immunopathologic resolution property of kolaviron in mice influenza pneumonitis

Abstract: Implicated in influenza-associated pathology are innate defence overzealousness and unabated secretion of oxidative tissue-sensitive antimicrobial agents. At different time points, mice were pre-treated with kolaviron (400 mg/kg), a natural antioxidant and anti-inflammatory agent, and subsequently challenged with 2 LD influenza A/H3N2/Perth/16/09 virus. After euthanasia at day 6, blood, lungs, liver and spleen were collected and processed for biochemical, immunohistochemical and flow cytometric assessment of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…Although, caution must be exercised when inferring mouse model studies to humans especially in RSV and IAV infections, this study corroborates findings elsewhere that have described more severe infections during single RSV and IAV infections when compared with cases of viral co-infections (Diaz et al., 2015; Kuchar et al., 2015; Ljubin-sternak et al., 2016). Severe immunopathology and mortality caused by IAV infection has been widely attributed to sustained activation of innate immune responses that supposedly should elicit viral clearance but paradoxically contribute to pathology via a typically defined mechanism known as cytokine storm (Awogbindin et al., 2017; Gruta et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Although, caution must be exercised when inferring mouse model studies to humans especially in RSV and IAV infections, this study corroborates findings elsewhere that have described more severe infections during single RSV and IAV infections when compared with cases of viral co-infections (Diaz et al., 2015; Kuchar et al., 2015; Ljubin-sternak et al., 2016). Severe immunopathology and mortality caused by IAV infection has been widely attributed to sustained activation of innate immune responses that supposedly should elicit viral clearance but paradoxically contribute to pathology via a typically defined mechanism known as cytokine storm (Awogbindin et al., 2017; Gruta et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Kaempferol inhibits the NF-κB and MAPK pathways, leading to an increase in SOD activity, the attenuation of ROS levels, and H9N2induced acute LI [57]. Some ROS scavengers, such as polyphenols, may modulate the NF-κB and MAPK pathways and upregulate GSH biosynthesis through Nrf2 activation [154,172,[190][191][192][193][194]. The immune-regulatory properties of NAC and IV-induced pneumonia are [228] Qi et al [200] related to the inhibition of the p38 MAPK pathway [195].…”
Section: Other Small Moleculesmentioning
confidence: 99%
“…Quercetin decreases the production of superoxide in alveolar macrophages during IV infection [ 88 ] and exerts an antiviral activity by inhibiting HA2 during IV infection [ 189 ]. A bioflavonoid isolated from Garcinia kola seeds (kolaviron) exhibits strong anti-IV activity via an antioxidative pathway [ 190 ].…”
Section: Main Textmentioning
confidence: 99%
“…anti-inflammatory bioactivities of kolaviron (KV), a natural bioflavonoid derived from the edible but astringent Garcinia kola seed. [19][20][21] Substantial evidence have also shown that KV confers protection against hepatotoxicity and genotoxicity independently induced by potent hepatotoxicants 2-acetyl aminofluorene, aflatoxin B1, dimethyl nitrosamine, and ethanol. [22][23][24][25][26] These toxicants, similar to MWCNTs, 12,13,17 elicit hepatic injury through oxidative stress and pro-inflammatory response whereas the mechanism of protection conferred by KV is largely related to its antioxidant, anti-inflammatory, and antiapoptotic mechanisms.…”
Section: Avalanche Of Reports Have Demonstrated the Antioxidant Andmentioning
confidence: 99%
“…Avalanche of reports have demonstrated the antioxidant and anti‐inflammatory bioactivities of kolaviron (KV), a natural bioflavonoid derived from the edible but astringent Garcinia kola seed 19‐21 . Substantial evidence have also shown that KV confers protection against hepatotoxicity and genotoxicity independently induced by potent hepatotoxicants 2‐acetyl aminofluorene, aflatoxin B1, dimethyl nitrosamine, and ethanol 22‐26 .…”
Section: Introductionmentioning
confidence: 99%